2012
DOI: 10.1239/aap/1346955257
|View full text |Cite
|
Sign up to set email alerts
|

Sharpness in the k-Nearest-Neighbours Random Geometric Graph Model

Abstract: Let Sn, k denote the random graph obtained by placing points in a square box of area n according to a Poisson process of intensity 1 and joining each point to its k nearest neighbours. Balister, Bollobás, Sarkar and Walters (2005) conjectured that, for every 0 < ε < 1 and all sufficiently large n, there exists C = C(ε) such that, whenever the probability that Sn, k is connected is at least ε, then the probability that Sn, k+C is connected is at least 1 - ε. In this paper we prove this conjecture. As a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Since the first draft of this paper Falgas-Ravry [4] has answered this question in the affirmative provided that the probability that G is connected is not too small: more precisely he proves it whenever P(G is connected) = Ω(n γ ) (where γ is an absolute constant).…”
Section: Question 2 How Many Vertices Do Small Components Contain?mentioning
confidence: 99%
“…Since the first draft of this paper Falgas-Ravry [4] has answered this question in the affirmative provided that the probability that G is connected is not too small: more precisely he proves it whenever P(G is connected) = Ω(n γ ) (where γ is an absolute constant).…”
Section: Question 2 How Many Vertices Do Small Components Contain?mentioning
confidence: 99%
“…Remark 1. Theorem 1 of [7] showed that, for n large enough, we need to increase k by at most a constant times log(1/ε) for S n,k to go from having an ε chance of being connected to having a 1 − ε chance of being connected. Assuming there is a 'bluntness' converse to this result, i.e.…”
Section: Results Of the Papermentioning
confidence: 99%
“…These results were substantially improved by Balister, Bollobás, Sarkar and Walters in a series of papers [3,5,4] in which they established inter alia the existence of a critical constant c ⋆ : 0.3043 < c ⋆ < 0.5139 such that for c < c ⋆ and k ≤ c log n, S n,k is whp not connected while for c > c ⋆ and k ≥ c log n, S n,k is whp connected. Building on their work, Walters and the author [7] recently proved that the transition from whp not connected to whp connected is sharp in k: there is an absolute constant C > 0 such that if S n,k is connected with probability at least ε > 0 and n is sufficiently large, then for k ′ ≥ k + C log(1/ε), S n,k ′ is connected with probability at least 1 − ε.…”
Section: Previous Work On the K-nearest Neighbour Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For any D as above, it is easy to show (see e.g. Lemma 8 of [19]) that the boundary of D meets at most 18πr 1)) n log n πr 2 . Since by construction of the random variable X − and X + we have that T (X − ) ≤ T (X) ≤ T (X + ), we deduce that whp the covering time for the torus V satisfies T (X) = (1 + o(1)) n log n πr 2 .…”
Section: Covering a Square With Random Discsmentioning
confidence: 99%